P-357 Predicting live birth following single euploid frozen blastocyst transfer - does the journey matter?. (30th June 2022) - Theodorou, E; Cardenas Armas, D; Chronopoulou, E; Jones, B.P; Ozturk, O; Serhal, P; Ben Nagi, J
Abstract: Study question: Does the number of available euploid embryos affect the success rate of the first single euploid frozen thawed embryo transfer (FTET)? Summary answer: The live birth rate (LBR) following the first single euploid FTET is independent of the number of available euploid embryos. What is known already: Preimplantation testing for aneuploidy (PGT-A) is a controversial laboratory technique as an embryo selection tool to increase LBR per transfer and reduce time to pregnancy. There have been many efforts to identify factors predictive of LBR following a euploid embryo transfer. The number of euploid embryos available is known to increase the expected cumulative LBR. However, there is lack of evidence whether the number of available euploid embryos is also significantly associated with chances of live birth for the first euploid FTET cycle. This is important for individualized patient counselling. Study design, size, duration: A retrospective analysis of the first, single, euploid FTET of 506 women, between January 2015 to March 2020 following PGT-A was carried out. The indication for PGT-A was advanced maternal age, recurrent miscarriage or implantation failure. Embryos were biopsied on day 5 or 6 and tested with array comparative genetic hybridization or next generation sequencing. The FTET outcomes were compared based on the number of euploid embryos available. Participants/materials, setting, methods: 198 women had one euploid embryo available (group 1), 120 women had two (group 2) and 188 women had three or more (group 3). Baseline characteristics were analysed for all participants to adjust for confounders. Reproductive outcomes such as pregnancy rate (PR), clinical miscarriage rate and LBR were compared between the 3 groups for the first euploid FTET. Univariate analysis with Kruskal-Wallis H, chi-square and multivariate logistic regression was performed with SPSS. Main results and the role of chance: Baseline characteristics were similar between the groups including age at egg collection (EC), body mass index, use of partner or donor sperm, method of insemination, number of ECs, endometrial preparation protocol and endometrial thickness prior to transfer. Women with three or more euploid embryos were younger at the time of EC compared to groups 1 and 2 (mean age 37 vs 39 and 38). The number of oocytes per EC (15 vs 11 and 11, p < 0.001), the total number of oocytes following batching cycles (20 vs 15 and 16, p < 0.001) and the number of blastocysts biopsied (8 vs 4 and 5, p < 0.001) were significantly higher for Group 3 vs Group 1 and Group 2, respectively. Group 1 embryos were less frequently of excellent and very good morphology and less frequently biopsied on day 5 vs 6. Univariate analysis suggests Group 3 had statistically higher PR and LBR compared to Group 1, but similar miscarriage rate. However, when applying a multivariate logistic regression model, the LBR after first euploid FTET was independent of the number of euploid embryos available but was influenced by age at EC (p = 0.006) and biopsy day (Day 6 vs day 5, OR 0.53, 95% CI 0.33-0.85, p = 0.008). Limitations, reasons for caution: The main limitation of this study is its retrospective nature performed in a single centre, and therefore vulnerable to bias and confounding factors that may have not been accounted for. Wider implications of the findings: Our findings suggest that the success rate of the first euploid FTET does not depend on the number of euploid embryos but is influenced by the age at EC and the embryo stage at biopsy. This could be useful when counselling women with a low number of euploid embryos available. Trial registration number: Not Applicable